STUDIES ON THE INFECTION OF YAMS BY SCUTELLONEMA BRADYS (STEINER AND LEHEW) (1975)
A general survey of phytoparasitic nematodes associated with yam (Dioscorea spp.) in the Mid-Western State of Nigeria showed that Seutellonema bradys and Meloidogyne spp. were the economically important nematodes of yam tubers. S. bradys was associated with the ’dry rot' of yam tubers causing storage losses estimated between 80 and 100%. Nematodes of the genus Meloidogyne were found associated with galling of tubers of water yam (D. alata). Studies on the rate of population build-up of S. bradys in storage showed that S. bradys increased 9-fold, 8-fold and 5-fold in the tubers of D. rotundata, D. cayenensis and D. alata respectively during 6 months of storage. These increases in population influenced the severity of ’dry rot’ disease. Results of investigations into the depth of penetration of S. bradys in 5 different varieties of D. rotundata showed that there were differences in varietal susceptibility. The bulk of the nematode population was found in the periderm to a depth of between 0-1.5 cm, but depth of penetration was greater in the head portions of each of the tubers than either the middle or bottom portions. Observations on the activities of the nematodes in tuber tissues (histopathology) suggested that the 'dry rot' was mainly due to mechanical damage to the cells and the host reaction to intracellular feeding by S. bradys. Studies on changes in the carbohydrate constituents of the yam tuber infected by S. bradys showed an increase in the percentages of monosaccharides and disaccharides like sucrose, glucose and galactose, fruobose with a concomitant decrease in starch, amylose and amylopectin when compared with healthy yam. Qualitative and quantitative determination of amino acid constituents of nematode-infected tubers of white yam (D. rotundata). yellow yam (D. cayenensis) and water yam (D. alata) showed that the relative numbers of free amino acids were not materially changed following infection by 5, bradys. but a reduction occurred in the number of 'essential' amino acids in the infected tubers. Eighteen ninhydrin positive amino acids were detected in the protein hydrolysate. Except in the case of white yam and in a few other cases, increases in protein amino acids were recorded in the infected tubers of yellow and water yam. The percentage protein was also increased by infection in all species except white yam (D. rotundata). Observations on the rate of weight loss (cumulative percentage weight and mean percentage weight loss) in 3 different species of Dioscorea stored in a yam barn showed that there was a significant difference in the rate of weight loss between nematode-infected and nematode-free tubers of D. rotundata and D. cavenensis, but no significant difference was recorded between the infected and healthy yam tubers of D. alata. Estimation of the edible portions in nematode-infected and nematode-free tubers of D. rotundata. D. cavenensis and D. alata showed a significant difference in the percentage peeling losses between the infected and healthy tubers. Chromatographic analysis of the incubation solution of S. bradys showed that 5 amino acids - aspartic acid, phenylalanine, hydroxylnol acetic acid, leucine and isoleucine were discharged by this nematode. The absence of the steroid group of compounds in the nematode-infected yam tubers revealed by spectrometrie analysis might be disease-related as evidenced by its appearance in the healthy tubers. Polygalacturonase and amylase activities were detected in homogenates of S, bradys. Studies on fungi associated with the dry rot disease of yam tubers showed Aspergillus niger. Penicillium sclerotigenum. Triohoderma viride. Rhizopus nigricans and Fusarium oxvsporum. Botrvodiplodia theobromae and Fusarium moniliforme as the main species. Studies on the possible interrelationshipsbetween S. bradys and 3 fungi A. niger. P. sclerotigenum and F. oxysporum showed that the presence of the nematode seemed to increase the degree of pathogenicity of Fusarium and Penicillium species on yams. But the presence of S. bradys did not increase the degree of pathogenicity of Aspergillus niger. In greenhouse experiments, the interaction between S. bradvs and A. niger was found to be disadvantageous to the nematode. The presence of the fungus seemed to have some effect on the number of nematodes that invaded the roots and tubers and subsequently on nematode development. This was thought to be due to an anti-biotic action of A. niger on S. bradys. A host range study of 30 crop plants and weeds revealed that beniseed (Sesamum indicum L.), cowpea (Vigna unguioulata (L.) Walp.), were good alternative hosts of S. bradys. Small populations of the nematode also survived endoparasitically in the roots of Bupatorium. avnedrella. roselle faib1scus sab dar if f a L.). kenaf (Hibiscus cannabinus L.), melon (Cucurbita pepo L.); jute (Corchorus olitorius L.); yam bean (Sphenostylis stenocarpa) (Hochst ex A Rich) Harms., soko (Oelosia araentia L.) and pigeon pea (Ca.lanus ca.ian (L.) Druce). Non-hosts included maize and tobacco. Dipping nematode-infected tubers of D. alata and D. cayenensis in hot water at temperatures ranging between 50 and 60°C for 40 minutes completely eliminated the nematode. However, at temperatures above 55°C for an exposure time of 1+0 minutes, the tubers so treated suffered a physiological damage and rotted very rapidly. Temperatures between 50 and 55°C had no adverse effect on percentage emergence, growth, yield and palatability of tubers of D. alata. Field trials on chemical and cultural control of S. bradys on D. alata showed that the yield of yam was increased and the nematode population suppressed by the application of organic manure at the rate of 1.5 kg/heap or 1 ,886.3 kg/ha. Although the application of nemagon at the rate of 35.2 kg/ha. considerably suppressed nematode population, the yield of yam was significantly reduced. The results showed that there is a good deal of potential for experimentation with various cultural methods of nematode control. Studies on the effect of gamma irradiation on S. bradys showed that dosages between 5 and 15 Krad did not eliminate the nematodes completely, but suppressed sprouting and signs of deterioration in tubers. Dosages between 20 - 30 Krad eliminated about 70 - 80% of the nematode population.